THE EFFECT OF INFORMATION QUALITY, INFORMATION QUANTITY, INFORMATION CREDIBILITY, INFORMATION ADOPTION ON UBW’S PURCHASE INTENTION IN SURABAYA - Harsono, Florencia Jusi (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study aims to determine the influence of Information Quality, Information Quantity, Information Credibility (X) on Purchase Intention (Y) with Information Adoption (Z) as an intervention variable in UBW in Surabaya. The sample size in this study was carried out using the Slovin formula of 210 respondents. The sampling technique uses purposive sampling. Data was obtained using a questionnaire measured by the Likert scale. This study uses PLS SEM analysis to analyze structural models and measurements. Based on the results of the study, Information Quality, Information Quantity, Information Credibility have a significant effect on UBW Information Adoption and Information Quality, Information Quantity, Information Credibility have a significant effect on UBW Purchase Intention, however Information Adoption did not have a significant effect on UBW’s Purchase Intention.UBW Purchase Intention, Information Quality does not have a significant effect on Purchase Intention through Information Adoption, Information Quantity does not have a significant effect on Purchase Intention through Information Adoption, Information Credibility does not have a significant effect on Purchase Intention through Information Adoption.